Pelatihan Teknik Komunikasi Efektif Pada Kader Keluarga Berencana Di Desa Panggungharjo - Retno Heru Setyorini; Andina Vita Sutanto (J.Abdimas: Community Health, 2021)
Communication is the most important key to building a good relationship between everyone. Delivering messages orally or in writing expects someone to be able to read or hear what is being said correctly. Effective communication is highly dependent on a person's skills in sending and receiving messages. The purpose of this community service is to improve the ability of cadres to communicate effectively to support their duties as family planning cadres. Implementation of activities by providing material on effective communication to 50 cadres in Panggungharjo Village using lecture, question and answer methods, and roleplay, using LCD Projector and Power Point media. Many participants asked questions related to effective communication techniques to solve problems and obstacles encountered in the field when providing communication, information, and education (CIE), as well as when motivating couples of childbearing age to use contraception. Effective communication training that explains the meaning, purpose, benefits of communication and barriers to communication can improve the ability of cadres to communicate effectively.